2021
DOI: 10.3390/diagnostics11061054
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Cytokine-Induced Apoptosis Inhibitor 1 (CIAPIN1) as a Potential Prognostic Biomarker of Cholangiocarcinoma

Abstract: The mortality rate of cholangiocarcinoma (CCA) is high since there is a lack of a non-invasive technique to accurately detect tumors at the early stage. CCA biomarkers are consistently needed for various purposes including screening, early diagnosis, prognosis and follow-up. Herein, using bioinformatic analysis of our mitochondrial proteome database of CCA tissues, we identified cytokine-induced apoptosis inhibitor 1 (CIAPIN1) as a potential prognostic biomarker for CCA. CIAPIN1 levels in the sera of 159 CCA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The Western blot analysis was performed for the detection of CIAPIN1 protein in CCA cell lysate as described previously [7]. Briefly, cells were lysed with lysis buffer (Cat#9806, RIPA, Cell Signaling Technologies, Danvers, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The Western blot analysis was performed for the detection of CIAPIN1 protein in CCA cell lysate as described previously [7]. Briefly, cells were lysed with lysis buffer (Cat#9806, RIPA, Cell Signaling Technologies, Danvers, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In the previous study of our group, Chua-On et al identified a total of 281 mitochondrial proteins, 105 of which were overexpressed in the cancerous tissue of CCA compared with adjacent non-cancerous tissues [6]. Among them, cytokine-induced apoptosis inhibitor 1 (CIAPIN1) was identified as a potential prognostic biomarker for CCA [7]. In particular, the serum CIAPIN1 level was significantly higher in CCA patients with lymph node metastasis than those without metastasis [7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The serum has also emerged as a biospecimen towards prognostic biomarkers exploration (Table 3 ). As such, high levels of tissue Krebs von den Lungen 6 (KL-6 mucin)[ 63 ], cadherin-17 (CDH17)[ 64 ], kallikrein-11[ 65 ], uPAR[ 59 ] and high levels of serum cytokine-induced apoptosis inhibitor 1 (CIAPIN1)[ 66 ], MUC5AC[ 55 ], OPN[ 50 ], S100A6[ 67 ] and uPAR[ 59 , 68 ] were found adverse prognostic factors for CCA patient’s survival. Subjected to meta-analysis, high levels of tissue PD-L1[ 17 ] and tissue protein S100P[ 69 ] were also proposed as potential prognostic markers of CCA.…”
Section: Proteinsmentioning
confidence: 99%
“…For instance, apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX-1) was a secreted protein which identified as a potential serum marker for diagnosis and prognosis of CCA ( 16 ). Moreover, other members of our group identified coiled-coil domain containing 25 (CCDC25), apoptosis-inducing factor, mitochondrion-associated 3 (AIFM3) and cytokine-induced apoptosis inhibitor 1 (CIAPIN1) as potential secreted protein biomarkers in CCA ( 17 19 ). In this study, we performed liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis of CCA patients' sera who were pathologically diagnosed with both vascular invasion and lymph node metastasis with ≤ 1 year survival time and >1 year survival time for searching a potential prognostic biomarker of CCA.…”
Section: Introductionmentioning
confidence: 98%